2016
DOI: 10.1093/mnras/stw2714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiative feedback on disc fragmentation

Abstract: Protostellar discs may become massive enough to fragment producing secondary lowmass objects: planets, brown dwarfs and low-mass stars. We study the effect of radiative feedback from such newly-formed secondary objects using radiative hydrodynamic simulations. We compare the results of simulations without any radiative feedback from secondary objects with those where two types of radiative feedback are considered: (i) continuous, and (ii) episodic. We find that: (i) continuous radiative feedback stabilizes the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 125 publications
(184 reference statements)
1
39
0
Order By: Relevance
“…Further, this allows the formation of low-mass stars, brown dwarfs, and planetary-mass objects through fragmentation of the protostellar disk. This mechanism in turn highlights that the interval between accretion episodes may be critical for determining the low-mass end of the initial mass function (Stamatellos et al 2011;Mercer & Stamatellos 2016).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, this allows the formation of low-mass stars, brown dwarfs, and planetary-mass objects through fragmentation of the protostellar disk. This mechanism in turn highlights that the interval between accretion episodes may be critical for determining the low-mass end of the initial mass function (Stamatellos et al 2011;Mercer & Stamatellos 2016).…”
Section: Introductionmentioning
confidence: 95%
“…One of the most important parameters in the episodic accretion process is the time interval between two accretion bursts because this timescale moderates the effect of radiative feedback on disk fragmentation (Mercer & Stamatellos 2016). Disk fragments may later be ejected, forming a proto-brown dwarf (Reipurth & Clarke 2001;Bate et al 2002;Rice et al 2003;Stamatellos & Whitworth 2009;Basu & Vorobyov 2012), or fall onto the central star, causing an accretion burst (Vorobyov & Basu 2005, 2010Dunham & Vorobyov 2012), or migrate to a stable orbit, resulting in a multiple system.…”
Section: Timeline Of the Episodic Accretion Processmentioning
confidence: 99%
“…Tobin et al (2016) found that the triple protostar system L1448 IRS 3B, which is classified as a Class 0 YSO, has the spiral structures. A compact multiple stellar system with spiral arms would be explained by fragmentation of the gravitationally unstable disk (Stamatellos & Whitworth 2009;Nayakshin 2010;Vorobyov & Basu 2010a;Tsukamoto et al 2015c;Mercer & Stamatellos 2017). Although the degree of ubiquity of spiral structures is still unclear, these observations suggest the importance of investigating gravitationally unstable disks in Class 0/I YSOs in greater detail.…”
Section: Empirical Formula Of Dust-to-gas Mass Ratio For a Gravitatiomentioning
confidence: 99%
“…Additionally, instabilities, taking place within the protostellar disc, have also been widely proposed, e.g. thermal instabilities (Bell et al 1995;Clarke & Syer 1996;Lodato & Clarke 2004), gravitational instabilities (Vorobyov & Basu 2005, and a combination of gravitational instabilities and the magneto-rotational instability (Armitage et al 2001;Zhu et al 2009aZhu et al ,b, 2010aStamatellos et al 2011;Mercer & Stamatellos 2017).…”
Section: Introductionmentioning
confidence: 99%